2010
DOI: 10.1249/mss.0b013e3181c29e90
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the ActiGraph 7164 and the ActiGraph GT1M during Self-Paced Locomotion

Abstract: Purpose This study compared the ActiGraph accelerometer model 7164 (AM1) to the ActiGraph GT1M (AM2) during self-paced locomotion. Methods Participants n = 116, 18–73y, mean BMI = 26.1) walked at self-selected slow, medium, and fast speeds around an indoor circular hallway (0.47km). Both activity monitors were attached to a belt secured to the hip and simultaneously collected data in 60 second epochs. To compare differences between monitors, the average difference (bias) in count output and steps output were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
3
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 23 publications
7
94
3
2
Order By: Relevance
“…While similar to the older models from Actigraph, as it measures vertical acceleration, the GT1M differs as it employs a Micro-Electronical Mechanical System (MEMS) system to detect acceleration as opposed to the cantilever beam sensor used in earlier models (12). While some papers have found good cross-validation between this model in a laboratory setting (12,14) other studies state that the GT1M may be underestimating levels of activity suggesting an application of a correction factor (6). Although not presented in the results of this study, it is noted from post hoc analysis that the application of the 9% correction factor to the GT1M data at 15 s epochs would result in bias (SD) of 0.2 min (3.6), slightly less than the 0.7 min presented for the uncorrected data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While similar to the older models from Actigraph, as it measures vertical acceleration, the GT1M differs as it employs a Micro-Electronical Mechanical System (MEMS) system to detect acceleration as opposed to the cantilever beam sensor used in earlier models (12). While some papers have found good cross-validation between this model in a laboratory setting (12,14) other studies state that the GT1M may be underestimating levels of activity suggesting an application of a correction factor (6). Although not presented in the results of this study, it is noted from post hoc analysis that the application of the 9% correction factor to the GT1M data at 15 s epochs would result in bias (SD) of 0.2 min (3.6), slightly less than the 0.7 min presented for the uncorrected data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one study has suggested that the GT1M accelerometry output is 9% lower than the earlier Actigraph model (MTI-7164; 6) and recommends applying a correctional factor when comparing models. More recent studies have concluded that the models can be used interchangeably showing good cross-validation (12,14) and so in the current study the correction factor was not applied to the GT1M data. To calculate the cut points for the shorter epochs, the 60 s cut points were divided by 60 then multiplied to calculate the cut points for 15, 30, and 60 s epochs, as undertaken in earlier studies (22).…”
Section: Methodsmentioning
confidence: 99%
“…Corder et al (2) suggested a small bias (of around 9%), such that Actigraph models after the 7164 should be corrected by increasing their "raw counts" by about 9%. On the other hand some studies suggest less need for such a correction with less evidence of bias between old and newer models, and close agreement between newer models based on the same technology (9,20). The comparison between Actigraph and activPAL for the current study, therefore, used both corrected Actigraph data (increased by 9%) and the uncorrected data.…”
Section: Comparison Of Activpal Vs Actigraphmentioning
confidence: 91%
“…Though different accelerometer models have demonstrated comparability in trials for moderate and vigorous physical activity counts, 47 there appear to be differences at lower intensity levels that have implications for sedentary behavior measures. 48,49 To inform analyses, the accelerometer models are being compared in small studies, and correction algorithms to adjust for accelerometer model as well as for the difference between the ActiGraph and Actical, are being developed. All countries employed a 60-second epoch for storing data.…”
Section: Objectively-assessed Activity (Preferred)mentioning
confidence: 99%